Cyclic phosphatidic acid inhibits the secretion of vascular endothelial growth factor from diabetic human coronary artery endothelial cells through peroxisome proliferator-activated receptor gamma. (5th September 2015) - Tsukahara, Tamotsu; Tsukahara, Ryoko; Haniu, Hisao; Matsuda, Yoshikazu; Murakami-Murofushi, Kimiko
Highlights: Cyclic phosphatidic acid (cPA) potently inhibits neointima formation by inhibiting PPARγ. cPA suppressed PPARγ-mediated cell growth and migration in D-HCAECs. cPA inhibited VEGF expression resulting in suppressing cell growth and migration in D-HCAECs. cPA plays a regulatory role of PPARγ in the vascular processes. Abstract: Atherosclerosis is a disease characterized by building up plaques formation and leads to a potentially serious condition in which arteries are clogged by fatty substances such as cholesterol. Increasing evidence suggests that atherosclerosis is accelerated in type 2 diabetes. Recent study reported that high level of alkyl glycerophosphate (AGP) was accumulated in atherosclerotic lesions. The presence of this phospholipid in mildly oxidized low-density lipoprotein (LDL) is likely to be involved in atherogenesis. It has been reported that the activation of peroxisome proliferator-activated receptor gamma plays a key role in developing atherosclerosis. Our previous result indicates that cyclic phosphatidic acid (cPA), one of bioactive lipids, potently suppresses neointima formation by inhibiting the activation of peroxisome proliferator-activated receptor gamma (PPARγ). However, the detailed mechanism is still unclear. In this study, to elucidate the mechanism of the cPA-PPARγ axis in the coronary artery endothelium, especially in patients with type 2 diabetes, we investigated the proliferation, migration, and secretion of VEGF in human coronary artery endothelial cells from diabetes patients (D-HCAECs). AGP induced cell growth and migration; however, cPA suppressed the AGP-elicited growth and migration in D-HCAECs. Moreover, AGP increased VEGF secretion from D-HCAECs, and this event was attenuated by cPA. Taken together, these results suggest that cPA suppresses VEGF-stimulated growth and migration in D-HCAECs. These findings could be important for regulatory roles of PPARγ and VEGF in the vascular processes associated with diabetes and atherosclerosis.